Dampak Psikologis pada Perawat yang Mengalami Long Covid - Aisyah, Nurismi; Veny Elita; Riri Novayelinda (Indonesian Journal of Nursing Research (IJNR), 2023)
Long Covid is athe residual symptoms of COVID-19 that are still felt by the survivors. One of these survivors is nurses because many nurses are currently affected by COVID-19. Survivors can feel the psychological impact of Long Covid. This study aims to describe the psychological impact on nurses who experience Long Covid. Descriptive research with a sample of 90 nurses who experienced Long Covid was taken with a total sampling technique taking by considering the inclusion criteria, namely: Nurses who contracted COVID-19 in 2020 and 2021 who experienced sequelae of Long Covid. The data were processed using a simple descriptive test. The majority of respondents were in the age range of 26-54 years (97.8%). Most gender is female (73.3%). The most places of work are hospitals (83.3%), and the majority of respondents experienced one time confirmed COVID-19 (81.1%). The psychological problems experienced were anxiety (32.2%), stress (13.3%) and depression (4.4%). Based on the results of the study, it can be concluded that there is a psychological impact on nurses who experience Long Covid. It is hoped that nurses who experience Long Covid can overcome perceived psychological problems so that they do not experience a decline in daily performance. Abstrak Long Covid merupakan sisa gejala COVID-19 yang masih dirasakan oleh para penyintas. Salah satu survivor tersebut adalah perawat karena saat ini banyak perawat yang terdampak COVID-19. Para penyintas dapat merasakan dampak psikologis Long Covid. Penelitian ini bertujuan untuk mendeskripsikan dampak psikologis pada perawat yang mengalami Long Covid. Penelitian deskriptif dengan sampel 90 perawat yang mengalami Long Covid diambil dengan teknik pengambilan total sampling dengan mempertimbangkan kriteria inklusi yaitu: Perawat yang terjangkit COVID-19 tahun 2020 dan 2021 yang mengalami gejala sisa Long Covid. Data diolah dengan menggunakan uji deskriptif sederhana. Mayoritas responden berada pada rentang usia 26-54 tahun (97,8%). Jenis kelamin terbanyak adalah perempuan (73,3%). Tempat kerja terbanyak adalah rumah sakit (83,3%), dan mayoritas responden mengalami satu kali konfirmasi COVID-19 (81,1%). Masalah psikologis yang dialami adalah kecemasan (32,2%), stres (13,3%) dan depresi (4,4%). Berdasarkan hasil penelitian dapat disimpulkan bahwa terdapat dampak psikologis pada perawat yang mengalami Long Covid. Diharapkan perawat yang mengalami Long Covid dapat mengatasi masalah psikologis yang dirasakan sehingga tidak mengalami penurunan kinerja sehari-hari.